THE INFLUENCE OF BRAND AMBASSADOR AND PERCEIVED QUALITY ON PURCHASE DECISIONS INSTANT HIJAB RABBANI - Diah Pangestu, Septya; Suroija, Noor; Nugroho, Jati (Applied Accounting and Management Review (AAMAR), 2024)
This study aims to determine the influence of brand ambassador and perceived quality on purchase decisions of moslem hijab rabbani (case study on consumer of instant jilbab rabbani branch demak jawa tengah). The Data of the research is collected by interviews and questionnaires to 85 respondents by implementing sampling purposive and accidental sampling technique. Instruments testing is conducted by testing the validity and reliability. The research analysis data explored by multiple regression analysis.The results show that brand ambassador partially hasn”™t a significant influence on purchase decisions and the influence of perceived quality has a significant on purchase decisions. Simultaneously, brand ambassador and perceived quality have an influence on purchase decisions. Based on the result of calculation of regression it is obtained that Y = 10,416 + 0,144 X1+ 0,475 X2.The result of coefficients determination (R ²) between brand ambassador and perceived quality contributes jointly on purchase decisions by 52,1% while the remaining 47,9% is influenced by the other factors not discussed in this research.